Genetic risk variants associated with the criminal mind and profiling through innovative forensic science techniques (2023)
Mental illnesses have impacted various genetic and forensic studies to the point of altercations and arguments based on the true nature of these disorders. While many scientists blame genetic variants caused by simple changes in the DNA to be the cause of these illnesses, others argue on behalf of the environmental factors, which time and time again have produced changes in our way of thinking and behaving. By looking at all these components we are able to fully understand the elements that go into the human mind in order to recognize why we are susceptible to psychological changes and how they may alter our life as a whole. With the compiling of various studies during the last few years the main purpose of this monograph relies on comprehending criminalistic cases by looking into the illnesses that may cause these violent conducts. These illnesses which are generated solely by risk variants both hereditary and non hereditary, as well as natural factors that are common in this society. With the use of these studies we conclude that the once thought of damaged minds of various people may actually be just an unlucky combination of misplaced codons, parental history and life events that make people who they are and who they can become.